Inovasi Media Mobile Learning dalam Pembelajaran Computational Thinking bagi Calon Guru - Satrio, Adrie; Lathifah, Afra (Paedagogie, 2026)
This study aims to develop a mobile learning product designed to support computational thinking (CT) learning for prospective teachers. Mastery of CT is an important competency in the digital era because it plays a role in equipping students with systematic, logical thinking and problem-solving skills according to the demands of the 21st century. The development process refers to the Alessi and Trollip model which includes the stages of needs analysis, design, development, and product trials. Data collection was carried out through questionnaires given to material experts, media experts, and prospective teachers as trial respondents. The results of the study indicate that the developed mobile learning application meets the valid criteria based on the assessment of material experts and media experts with a very good/very feasible category. Trials on prospective teachers indicate that the application has a good level of practicality and is effective in improving knowledge about computational thinking. Thus, the developed mobile learning is suitable for use as an innovative and relevant learning medium to support strengthening prospective teachers' CT abilities.